The Metaphor of War in Political Discourse on COVID-19 in Uganda - Atuhura, Dorothy (Frontiers in Communication, 2022)
The article examines the use of the metaphor of war in political communication on the novel Covid-19 pandemic in Uganda using two analytical tools of the social representation theory, anchoring and objectification. Drawing data for analysis from Uganda’s President, Y.K. Museveni’s televised national addresses to the country in 2020, the paper argues that during the time of the Covid-19 pandemic, there was a persistent dominant use of the metaphor of war by government representatives as a rhetorical device to conceptualize and communicate about an emerging unknown virus as a threat that should be managed through combat behavior. In so doing, the use of the war metaphor and its implied call for combat behavior to control, eradicate, and manage the virus spread engendered consequences such as standardizing hegemonic understanding of the nature and causes of the virus as well as naturalizing and legitimizing aggressive militaristic interventions that the government adopted to manage it.